Vocabulary of clothing in EFL coursebooks - Boháčová, Hana (2007)
In this diploma thesis vocabulary of clothing in EFL coursebooks is studied. Based on the secondary resources a large theoretical insight into the principles of vocabulary teaching and learning has been produced. In the second part a research into the teaching of vocabulary of clothing in various coursebooks has been carried out and the results depicted in the form of an analysis table. The sample for the analysis had to be narrowed down to the coursebooks of general British English for adult and young adult EFL learners published by Oxford University Press, Cambridge University Press, Macmillan and Pearson Longman after the year 1990. The total number of coursebooks selected amounted to twenty. The analysis criteria were based on the findings from the theoretical framework. Ten categories and numerous features of vocabulary teaching were created and all the coursebooks have been analyzed for which of those features they include and which are omitted. The findings have been interpreted